Two new records for the agrostological flora of Peru - Muñuico, Jhon W. (2024)
The presence of Piptochaetium bicolor (Vahl) É.Desv. and Trichachne californica var. villosissima (Henrard) Wipff & R.B. Shaw are recorded for the first time based upon collections made in the lomas formations of the Department of Arequipa. Piptochaetium bicolor has a recorded distribution as native to Argentina, Brazil, Chile, and Uruguay. Trichachne californica has a recorded distribution as native to southwestern US, Mexico, Caribbean, and through South America and its var. villosissima has been recorded previously from Argentina, Bolivia, Caribben, Colombia, Paraguay and Venezuela. Descriptions, photographs and illustrations are presented for each taxon.